Mirette on the high wire - McCully, Emily Arnold (New York : c, 1992)
Mirette learns tightrope walking from Monsieur Bellini, a guest in her mother's boarding house, not knowing that he is a celebrated tightrope artist who has withdrawn from performing because of fear.
Keywords: Caldecott Medal; Tightrope walking -- Fiction